Transnational Education: An Australian Approach to Assuring Quality and Engaging Offshore Staff - Soontiens, Werner; Pedigo, Kerry (Business Education and Accreditation, 2013)
Traditionally and despite the growth and increased importance of transnational education (TNE) staff development and induction in offshore locations are undertaken from afar with sporadic actual engagement. As a long time TNE provider, in an often complex environment, the Curtin Business School (CBS) at Curtin University, in Perth, Western Australia has developed and is implementing a multifaceted approach to the induction of offshore staff. The article reflects on the context, roll-out and results of a newly developed residential staff induction program. The program facilitated skill development and understanding but more importantly established an unanticipated depth of connectedness and commitment.